2016
DOI: 10.3762/bjoc.12.183
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and NMR studies of malonyl-linked glycoconjugates of N-(2-aminoethyl)glycine. Building blocks for the construction of combinatorial glycopeptide libraries

Abstract: SummaryFour glycoconjugate building blocks for the construction of combinatorial PNA like glycopeptide libraries were prepared in 75–79% yield by condensing tert-butyl N-[2-(N-9-fluorenylmethoxycarbonylamino)ethyl]glycinate (AEG) 5 with 3-oxo-3-(2,3,4,6-tetra-O-acetyl-β-D-glucopyranosylamino)- (6a), 3-oxo-3-(β-D-galactopyranosylamino)- (6b), 3-oxo-3-(2-acetamido-2-deoxy-3,4,6-tetra-O-acetyl-β-D-glucopyranosylamino)- (6c) and 3-oxo-3-(2-acetamido-2-deoxy-3,4,6-tetra-O-acetyl-β-D-galactopyranosylamino)propanoic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The glycosylated aspartic acids 3 (except for 3d and 3f) were prepared previously with the help of different types of coupling reagents, such as benzotriazol-1-yloxytris(dimethylamino)phosphonium hexafluorophosphate (BOP) or diisopropyl carbo- diimide (DIC) and additives, such as 1-hydroxybenzotriazole (HOBt) or triethylphosphine. [29][30][31] However, in our hands, none of the described methods reached the high yields that we previously obtained with the onium salt-mediated peptide cou-pling protocol with O-(7-azabenzotriazol-1-yl)-N,N,N′,N′-tetramethyluronium hexafluorophosphate (HATU) or with 2-(1Hbenzotriazol-1-yl)-1,1,3,3-tetramethyluronium hexafluorophosphate (HBTU, Scheme 2 and Table 1) [6,32]. Here, we com- pared the condensation with HBTU and HATU for the preparation of the glycosyl amino acids 3a-f since previous studies showed HATU to be more efficient than HBTU in similar cases [33][34][35].…”
Section: Resultsmentioning
confidence: 70%
“…The glycosylated aspartic acids 3 (except for 3d and 3f) were prepared previously with the help of different types of coupling reagents, such as benzotriazol-1-yloxytris(dimethylamino)phosphonium hexafluorophosphate (BOP) or diisopropyl carbo- diimide (DIC) and additives, such as 1-hydroxybenzotriazole (HOBt) or triethylphosphine. [29][30][31] However, in our hands, none of the described methods reached the high yields that we previously obtained with the onium salt-mediated peptide cou-pling protocol with O-(7-azabenzotriazol-1-yl)-N,N,N′,N′-tetramethyluronium hexafluorophosphate (HATU) or with 2-(1Hbenzotriazol-1-yl)-1,1,3,3-tetramethyluronium hexafluorophosphate (HBTU, Scheme 2 and Table 1) [6,32]. Here, we com- pared the condensation with HBTU and HATU for the preparation of the glycosyl amino acids 3a-f since previous studies showed HATU to be more efficient than HBTU in similar cases [33][34][35].…”
Section: Resultsmentioning
confidence: 70%
“…N -(ω-Aminoalkylene)amino acids have many interesting biological activities and play important roles in medicinal chemistry and drug discovery for the pharmaceutical industry. 1–4 In biochemistry, N -(ω-aminoalkylene)amino acids, such as N -(2-aminoethyl)glycine I , are used for the synthesis of peptide nucleic acids (PNAs) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33] However, this reaction protocol can likewise be used for other natural or unnatural amino acids, which our laboratory could show earlier. [34][35][36]…”
mentioning
confidence: 99%